2019
DOI: 10.1111/1462-2920.14579
|View full text |Cite
|
Sign up to set email alerts
|

Diatoms shape the biogeography of heterotrophic prokaryotes in early spring in the Southern Ocean

Abstract: Summary The interplay among microorganisms profoundly impacts biogeochemical cycles in the ocean. Culture‐based work has illustrated the diversity of diatom–prokaryote interactions, but the question of whether these associations can affect the spatial distribution of microbial communities is open. Here, we investigated the relationship between assemblages of diatoms and of heterotrophic prokaryotes in surface waters of the Indian sector of the Southern Ocean in early spring. The community composition of diatom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
42
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(47 citation statements)
references
References 81 publications
(156 reference statements)
5
42
0
Order By: Relevance
“…These taxonomic differences likely reflect the higher light attenuation of this shallower site and the constant stream of organic material and nutrient inputs that are delivered to these sediments from the Yarra River (Harris et al 1996). Known drivers of microbial community composition (pH, moisture content, organic carbon and N content, chlorophyll α and NH 4 + -N) (Jorgensen et al 2012, Fortunato et al 2013, Fagervold et al 2014, Probandt et al 2017, Wang et al 2018, Liu et al 2019) varied between these sampling sites, and in conjunction with previous research our study supports the findings that HB and CPPB represent both biogeochemically (Murray & Parslow 1999) and microbial distinct sediment habitats.…”
Section: Spatial Differences In Sediment Microbial Community Composition and N-cycling Capacitysupporting
confidence: 90%
“…These taxonomic differences likely reflect the higher light attenuation of this shallower site and the constant stream of organic material and nutrient inputs that are delivered to these sediments from the Yarra River (Harris et al 1996). Known drivers of microbial community composition (pH, moisture content, organic carbon and N content, chlorophyll α and NH 4 + -N) (Jorgensen et al 2012, Fortunato et al 2013, Fagervold et al 2014, Probandt et al 2017, Wang et al 2018, Liu et al 2019) varied between these sampling sites, and in conjunction with previous research our study supports the findings that HB and CPPB represent both biogeochemically (Murray & Parslow 1999) and microbial distinct sediment habitats.…”
Section: Spatial Differences In Sediment Microbial Community Composition and N-cycling Capacitysupporting
confidence: 90%
“…The correlations we obtained between a given diatom species and prokaryotic taxa and vice versa were multiple, suggesting that the majority of these associations reflect non‐specific interactions. On the one hand, phytoplankton was shown to explain changes in heterotrophic prokaryotic communities better than environmental parameters on temporal and spatial scales (Lima‐Mendez et al ., 2015; Needham and Fuhrman, 2016; Liu et al ., 2019). On the other hand, the production of common biologically labile substrates is in part independent of the phytoplankton assemblage and was suggested to explain recurrent patterns in prokaryotic community composition (Teeling et al ., 2016).…”
Section: Discussionmentioning
confidence: 99%
“…The release of a suite of organic compounds by phytoplankton and their processing by diverse taxa is one of the driving processes (Moran et al ., 2016; Mühlenbruch et al ., 2018). The various interactions between phytoplankton species and microbial taxa could additionally lead to shifts in community composition (Amin et al ., 2012; Lima‐Mendez et al ., 2015; Liu et al ., 2019). Long‐term observations are key to identify these patterns and to detect changes in the functioning of microbial communities due to global environmental change.…”
Section: Introductionmentioning
confidence: 99%
“…This suggests the occurrence of a bacterioplankton succession that responds to the increase of diatom-derived DOM by the increase in the bacterial production rates, but also responds to a niche partitioning of the highly diverse bacterial community that exploits different resources. Other studies have also reported higher bacterial diversity during the spring bloom dominated by diatoms in the Baltic Sea and Southern Ocean (Lindh et al 2015;Liu et al 2019). However, there are also contradictory findings with, for example, lower diversity with an increase in Chl a during a Phaeocystis antarctica bloom (Richert et al 2019) and also lower diversity with an increase in PP (Raes et al 2011).…”
Section: Links Between Bacterial Community Composition and Ecosystem mentioning
confidence: 96%